Optimization and Control for Systems in the Big-Data Era Theory and Applications - Choi, Tsan-Ming; Gao, Jianjun; Lambert, James H.; Ng, Chi-Kong; Wang, Jun (International Series in Operations Research & Management Science, 2017)
X, 280 p. 34 illus., 30 illus. in color.